Daura Al-Lugatu Al-‘Arabiyyah Fī Tafsīri Al-Qur’āni Li Muḥammadin Abū Zahrah: Dirāsatun Fī Zahrati At-Tafāsīri - Moh Abdul Kholiq Hasan (UIN Sunan Kalijaga Yogyakarta, 2023)
The significance of Arabic in the interpretation of the Qur'an is noteworthy from both classical and contemporary perspectives. Among contemporary interpreters, Abu Zahrah stands out for his exceptional focus on Arabic in his interpretation. Although Abu Zahrah's approach to language is similar to that of other commentators like al-Zamakhsyari, the results of his interpretation show significant differences. This research aims to examine the role of Arabic in Abu Zahrah's interpretation and how he addresses various linguistic challenges through qualitative descriptive research and content analysis. The findings revealed that Arabic played a highly significant role in Zahrah al-Tafāsīr's interpretation, becoming one of the main pillars. The study explored linguistic themes such as Isytiqāq, Nahw, Ṣarf, al-Ḍamāir, 'Irāb, and Balāgah. Abu Zahrah's method in dealing with linguistic problems includes referencing the Qur'an and sunnah, employing a balanced linguistic approach, making definitive choices, finding middle grounds between diverse opinions, and critiquing views deemed incorrect. Despite evident influence from al-Zamakhsyari, Abu Zahrah remains critical of his ideas. The evidence of Abu Zahrah's proficiency in Arabic is undeniable.